Gerações de professoras de escolas de classes multisseriadas do campo - Moreto, Charles (2015)
Deals with the formation and experienced work by different generations of teachers of multigrade schools classes in the county of Santa Teresa field, state of Espirito Santo. Seeks to know the collective guidance of teachers from different generations, expanding the possibilities for analysis and understanding the admission processes in career, training and work in such schools of the county in question. Used as theoretical framework the concept of generations produced by Karl Mannheim (1993). The participants were eleven (11) teachers from a universe of 13 (thirteen), as follows: a) Group 01 - made up of 06 (six) teachers born in the 1960s (one thousand, nine hundred and sixty) and with at least 20 (twenty) years of experience on multi-year classes of schools, calling itself the "Field Fighters" group. b) Group 02 - made up of 05 (five) teachers born from the second half of 1970 (one thousand, nine hundred and seventy) and 1980 (thousand nine hundred and eighty) and have a maximum of 10 (ten) years of experience with multi-year classes of schools, calling itself the "Field of Flowers" group. Looking to explicit in this study, through the analysis of data produced by the instruments, biographical narratives interviews SCHÜTZE 2011, 2014), forms and discussion groups (WELLER, 2006; 2011), which the collective guidance of the teachers working multigrade classes in the schools of Santa Teresa. To this end, the documentary employs the method initially developed by Karl Mannheim and reworked by Ralf Bohnsack (WELLER, 2005), as a method of analysis of the passages and narratives presented by informants who employing the following steps: a) formulated interpretation; b) reflected interpretation; c) comparative analysis, reaching d) building types and multidimensional analysis. Regarding the Discussion Groups "Field Fighters" and "Field of Flowers", the passages a) initial formation were analyzed; b) the profession of teaching (entry and initial experiences in career); c) perceptions of the school multisseriate class; d) teaching; e) generations of teachers of multigrade schools classes. In turn, for the biographical narrative interviews used in this work, it was considered: a) presentation; b) profession; c) training; d) teaching in the school of multigrade classes; and e) proposals for the field school. Identifying in the “Field Fighters” group informants, a community orientation, of which has the following components: a) a perception of the teacher and its work as a vocation, a process we call "mystification of choice"; b) a strong sense of duty (with each other), that in the cases in question are the managers that invited him to work, the communities, parents and the students, motivating them to take the role of agents in social transformation; c) selfdenial, through hard work and; d) opening to the search and the offer of help in overcoming the problems encountered. The bureaucratic and legalistic orientation was identified in the informants of the "Field of Flowers" group and is presented in the following components: a) diversification of training (initial and continuing) as a way to expand employment opportunities and help remain the competition in selection processes; b) building a repertoire of pedagogical practices based on "how to do it"; c) intensification of demands for income, especially from students; d) increasing demands on the teacher and its work. It concludes emphasizing that the informants worldviews in question have a great connection with the temporal context of the profession, linked to the local context and culture of the city where they lived (live) during their youth, their education and professional life. It further states that the debate over generations, to allow the reconstruction of the social trajectories of the teachers from previous generations, contributes to analyze and to understanding the collective action undertaken by the new generations as well as the challenges that they face. Thinking on the processes of identification and socialization of multigrade school teachers from the countryside classes in the positions and, more specifically, from the generational connections provides analyzes trends to change, and trends experienced by the “stays” of such teachers and the teaching profession, whether in Santa Teresa, as well as in the broader context of Brazilian society.